Cointegration vector estimation by dols for a three-dimensional panel (2015)
This paper extends the results of the dynamic ordinary least squares cointegration vector estimator available in the literature to a three-dimensional panel. We use a balanced panel of N and M lengths observed over T periods. The cointegration vector is homogeneous across individuals but we allow for individual heterogeneity using different short-run dynamics, individual-specific fixed effects and individual-specific time trends. We also model cross-sectional dependence using time-specific effects. The estimator has a Gaussian sequential limit distribution that is obtained by first letting T ? ? and then letting N ? ?, M ? ?. The Monte Carlo simulations show evidence that the finite sample properties of the estimator are closely related to the asymptotic ones. © 2015 Revista Colombiana de Estadística All rights received.